Field performance of cultivars of okra (Abelmoschus esculentus) under cultivar-specific seed priming - SHARMA, A D; RATHORE, S V S; SRINIVASAN, KALYANI; TYAGI, R K (The Indian Journal of Agricultural Sciences, 2016)
Seeds of three cultivars of okra (cv. A-4, Phule Utkarsha and VRO-6) were subjected to four seed priming methods, namely, hydropriming, osmopriming, halopriming and solid matrix (SM) priming comprising a total of 18 treatments of different priming combinations along with control. The observations of selected physiological parameters - seed germination, seedling vigour, vigour index, and field performance of three cultivars were recorded. Cultivar- specificity with reference to priming treatment was observed. On the basis of data recorded for the above parameters, hydropriming for 18 hr for cv. A-4, halopriming with 1% CaCl2 for 6 hr for cv. VRO-6 and SM priming with calcium aluminium silicate (1:0.4:1; Seed : SM : Water) for 48 hr for cv. Phule Utkarsha were found to be the most beneficial which could increase the fruit yield up to 20-104% in the three tested cultivars. The experiment underscored that to harness maximum benefit of seed priming for best field performance, cultivar-specific priming treatment should be adopted.